Diagnostic Accuracy of a Short Endoscopic Secretin Test in Patients With Cystic Fibrosis. Issue 8 (November 2015) - Engjom, Trond; Erchinger, Friedemann; Lærum, Birger Norderud; Tjora, Erling; Aksnes, Lage; Gilja, Odd Helge; Dimcevski, Georg
Abstract : Objective: Short endoscopic secretin tests for exocrine pancreatic function are not properly evaluated in cystic fibrosis (CF). Methods: Patients with CF and healthy controls (HCs) underwent endoscopic collection of duodenal juice between 30 and 45 minutes after secretin stimulation. Duodenal juice was analyzed for HCO3 − concentration and pancreatic enzyme activities. Stool was analyzed for fecal elastase. Results: Thirty-one patients with CF and 25 HCs were tested. Patients were classified as exocrine pancreatic sufficient (n = 13) or insufficient (n = 18). Both bicarbonate concentrations and enzyme activities in duodenal juice differentiated patients with CFI from patients with CFS and HC ( P < 0.001). The population displays strong correlation between severe CF genotype in both alleles and pancreatic insufficient phenotype ( P < 0.001). Conclusions: Pancreatic exocrine insufficient CF patients could be differentiated from exocrine sufficient patients and HCs using short endoscopic secretin test.